2004
DOI: 10.1523/jneurosci.3584-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Transplantation of Adult Mouse Neural Progenitor Cells into the Niemann-Pick-A Mouse Leads to a Marked Decrease in Lysosomal Storage Pathology

Abstract: Niemann-Pick disease is caused by a genetic deficiency in acid sphingomyelinase (ASM) leading to the intracellular accumulation of sphingomyelin and cholesterol in lysosomes. In the present study, we evaluated the effects of direct intracerebral transplantation of neural progenitor cells (NPCs) on the brain storage pathology in the ASM knock-out (ASMKO) mouse model of Type A Niemann-Pick disease. NPCs derived from adult mouse brain were genetically modified to express human ASM (hASM) and were transplanted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 43 publications
1
55
0
1
Order By: Relevance
“…7 and 8, which are published as supporting information on the PNAS web site) overlapped with areas that were positive for hASM immunostaining, indicating that each serotype vector was capable of generating a functional transgene product. As previously demonstrated (3,18), cholesterol clearance also occurred in areas anatomically connected with the injection site that did not stain positively for hASM. METAMORPH analysis indicated that a reduction in filipin staining occurred throughout the entire rostral-caudal axis.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…7 and 8, which are published as supporting information on the PNAS web site) overlapped with areas that were positive for hASM immunostaining, indicating that each serotype vector was capable of generating a functional transgene product. As previously demonstrated (3,18), cholesterol clearance also occurred in areas anatomically connected with the injection site that did not stain positively for hASM. METAMORPH analysis indicated that a reduction in filipin staining occurred throughout the entire rostral-caudal axis.…”
Section: Resultssupporting
confidence: 72%
“…Mice that were unilaterally injected with different AAV serotypes encoding for hASM were killed 7 weeks after injection (14 weeks of age) with euthasol (150 mg͞kg i.p.) and then either decapitated (n ϭ 5 per group) or transcardially perfused (n ϭ 3 per group) with fixative as described (18). Brains from decapitated mice were rapidly removed, snapfrozen in liquid nitrogen, dissected into three sections [right cerebral hemisphere, left cerebral hemisphere, and cerebellum (including the brainstem)], homogenized, and analyzed for hASM by ELISA (18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, SM has a strong affinity for cholesterol, reflected in its tight association in signaling platforms in the plasma membrane and intracellular organelles. Moreover, ASMko mice brains show cholesterol deposits 29,30 and the accumulation of this lipid impairs lysosomal function in different LSDs. 21,22,24 To test cholesterol involvement, NPA fibroblasts were incubated with methyl-b-cyclodextrin, which sequesters this lipid without affecting SM.…”
Section: Resultsmentioning
confidence: 99%